2023
DOI: 10.1128/msphere.00177-23
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing diversity and antagonism within the pig skin microbiota to identify novel mediators of colonization resistance to methicillin-resistant Staphylococcus aureus

Abstract: The microbiota mediate multiple aspects of skin barrier function, including colonization resistance to pathogens such as Staphylococcus aureus . The endogenous skin microbiota limits S. aureus colonization via competition and direct inhibition. Novel mechanisms of colonization resistance are promising therapeutic targets for drug-resistant infections, such as those caused by methicillin-resistant S. aureus (MRSA). Here, we developed and ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
7
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 51 publications
4
7
3
Order By: Relevance
“…This result differs from our previously reported data, where precolonization by D. incerta was not sufficient to reduce MRSA colonization but showed a trend toward statistical significance 24 . In our previous model we used a lower inoculum of D. incerta (10 8 CFU) on a different genetic background (SKH1 hairless mice).…”
Section: Resultscontrasting
confidence: 99%
See 3 more Smart Citations
“…This result differs from our previously reported data, where precolonization by D. incerta was not sufficient to reduce MRSA colonization but showed a trend toward statistical significance 24 . In our previous model we used a lower inoculum of D. incerta (10 8 CFU) on a different genetic background (SKH1 hairless mice).…”
Section: Resultscontrasting
confidence: 99%
“…In both models, 10 9 CFU D. incerta was applied daily for 2 days and 10 8 CFU USA300 MRSA was applied daily for one day. We found that precolonization with D. incerta reduced subsequent MRSA colonization by 60%, but decolonization with D. incerta did not have a noticeable effect on MRSA bacterial burden.This result differs from our previously reported data, where precolonization by D. incerta was not sufficient to reduce MRSA colonization but showed a trend toward statistical significance 24 . In our previous model we used a lower inoculum of D. incerta (10 8 CFU) on a different genetic background (SKH1 hairless mice).…”
contrasting
confidence: 99%
See 2 more Smart Citations
“…Consistent with previous works characterizing porcine skin microbial communities (Wareham- Mathiassen et al, 2023; Wei et al, 2023), bacterial communities are dominated by taxa within the Bacillota phyla and Aerococcus and Streptococcus genera ( Fig. 1E-F ).…”
Section: Discussionsupporting
confidence: 91%